Antimicrobial Sinergy Evaluation of Lactic Bacteria Strains Against Pathogens (Veterinary Science, 2023)
One of the most notable biological properties attributed to probiotics is their antimicrobial activity. Probiotics research has traditionally been focused on single strains, however, probiotic strains combinations can have a broader spectrum of action or synergistic effects, enhancing their protective action. The objective of this research was to evaluate the synergistic effect of lactic acid bacteria isolated from breast milk of different origins on the inhibition of bacterial pathogens of importance in human and animal medicine. Combinations of seven strains of lactic acidbacteria paired together were used and their inhibitory effect on bacterial pathogens Escherichia coli ATCC 25922, Salmonella enterica ATCC 13076, Klebsiella pneumoniae ATCC 13883, Acinetobacter baumannii ATCC 19606 and an enterohemorragic E. coli strain was investigated. The combination TUCO-5E + TUCO-L2 was the most effective in inhibiting the growth of all pathogens evaluated, highlighting its effect on K. pneumoniae y A. baumannii. Five of the evaluated combinations showed synergistic effects in the inhibition of extraintestinal pathogens: a) a synergistic effect was observed between strains TUCO-5E + TUCO-L2 for the inhibition of K. pneumoniae and A. baumannii, b) synergistic effect for TUCO-5E + TUCO-2, TUCO-5 + TUCO-2, and TUCO-3 + TUCO-17 on K. pneumoniae and, c) synergistic effect for TUCO-16 + TUCO-17 on A. baumannii. The combinations that showed synergy in the antimicrobial effect are good candidates for the development of multistrain probiotics for the prevention and treatment of specific bacterial infections
Keywords: Probiotics; Synergy; Lactobacillus; Antimicrobial Activity